Clinicopathological significance of matrix metalloproteinase-7 protein expression in esophageal cancer: a meta-analysis - Miao S; Zhou SY; Han CS; Zhang LN; Sun HB; Yang B (Dove Medical Press, 2015)
Shuai Miao,1 Shi-Yao Zhou,2 Chun-Shan Han,3 Le-Ning Zhang,3 Hong-Bin Sun,3 Bin Yang3 1Department of Geriatrics, China-Japan Union Hospital of Jilin University, 2Department of Clinical Medicine, Jilin University, 3Department of Thoracic Surgery, China-Japan Union Hospital of Jilin University, Changchun, People’s Republic of China Background: The MMP-7 basement membrane and extracellular matrix may be essential for tumor invasion and metastasis, and the results presented herein showed a relationship between MMP-7 expression and esophageal cancer (EC). However, its clinicopathological value for EC patients remains inconsistent. To clarify their associations, a meta-analysis of the relevant published literature was conducted.Materials and methods: Databases including PubMed, Embase, Web of Science, Cochrane Library, CISCOM, CINAHL, and Google Scholar were electronically searched. Only those studies analyzing MMP-7 expression in EC patients with regard to series of different demographic variables and clinicopathological stages (TNM stage, differentiation and invasion grade, and lymph-node [LN] metastasis) were eligible for inclusion. Summary odds ratios (ORs) were pooled in accordance with the random-effect model.Results: Fourteen clinical cohort studies (tumor samples =935) were incorporated into the current meta-analysis. Results revealed that increased MMP-7 expression in EC patients was positively correlated to TNM stage III–IV (OR 3.04, 95% confidence interval [CI] 1.43–6.46; P=0.004). Similar connections were also detected in the differentiation grade, invasion grade, and LN metastasis (all P<0.05). Country-stratified analysis yielded significant association of elevated MMP-7 expression with EC in the People’s Republic of China (PRC) under both TNM III–IV versus I–II and differentiation low versus high comparisons (TNM stage, OR 2.01, 95% CI 1.55–2.59, P<0.001; differentiation grade, OR 1.32, 95% CI 1.11–1.57, P=0.002). With regard to invasion grade and LN metastasis, significant association was observed in all the experimental subgroups (all P-values [PRC and Japan] were lower than 0.05).Conclusion: These data showed an obvious connection between MMP-7 and TNM stages, differentiation grade, invasive grade, and LN metastasis of EC, indicating that overexpression of MMP-7 may be a suitable diagnostic biomarker for variation in EC clinicopathological features. Keywords: MMP-7, esophagus carcinoma, statistical analysis